The Application of the Authentic Learning Model in Improving Fiqh Learning Achievement - Heri; Ach Fajri Zain; Nila Aula Fina; Ach Tajudin; Nur Halimah (Journal of Practice Learning and Educational Development, 2025)
This study aims to determine the Application of the Authentic Learning Model in Improving Fiqh Learning Achievement at Madrasah Tsanawiyah Al-Hasan Putri, Srambah Village, Proppo District, Pamekasan Regency. This research is motivated by the low academic performance of students in the subject of Fiqh, which is caused by a passive learning approach, teacher-centered methods, and a lack of real learning experiences. This condition makes students less motivated, less active, and have difficulty understanding the connection between the subject matter and everyday life. This model is expected to create an active, contextual, enjoyable, and meaningful learning atmosphere, thereby improving students' academic performance. This research uses a qualitative approach with a descriptive research type. Data collection techniques were carried out thru observation, interviews, and documentation involving the head of the madrasa, Fiqh subject teachers, and students as the main data sources. Data analysis was conducted thru the stages of data reduction, data presentation, and conclusion drawing. The research results show that the implementation of the Authentic Learning model in Fiqh education can improve students' performance, participation, and understanding. Students appear more active, enthusiastic, and able to relate the material to real-life experiences in their daily lives. Improvements are also seen in the students' learning evaluation results after this teaching model was implemented. Supporting factors for success include institutional support, facilities and infrastructure, teacher guidance and mentoring, teacher mastery of the material, and student engagement in the learning process. As for the inhibiting factors, they include the low level of student discipline, limited learning time, differences in students' ability to understand the material contextually, and the shyness of some students in expressing their opinions in class.